2018
DOI: 10.1007/s40692-018-0098-9
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Acceptance, Actual Use of a Virtual Learning Environment and Performance: An Ecological Approach

Abstract: The Technology Acceptance Model (TAM) is regularly used to investigate students' acceptance of virtual learning environments and the impact on students' intention to use. Past TAM studies barely investigated students' actual use of virtual learning environments, neither how actual use relates to their performance in an ecological valid educational context. In this study a Moodle-based virtual learning environment regarding teaching a foreign language is studied in a teacher education context. The instructional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 52 publications
2
9
0
Order By: Relevance
“…All variables except PEOU had a direct and significant influence on students’ attitudes towards e-learning usage. This result corroborates that by Larmuseau et al ( 2018 ) and Tiwari ( 2020 ) who found that attitude is significantly affected by the extent to which a given technology will make a user productive. Also in line with the postulation so the TAM (Davis 1989 ), when technology makes users productive, they will as well find it to be useful.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…All variables except PEOU had a direct and significant influence on students’ attitudes towards e-learning usage. This result corroborates that by Larmuseau et al ( 2018 ) and Tiwari ( 2020 ) who found that attitude is significantly affected by the extent to which a given technology will make a user productive. Also in line with the postulation so the TAM (Davis 1989 ), when technology makes users productive, they will as well find it to be useful.…”
Section: Discussionsupporting
confidence: 91%
“…Accordingly, PEOU was found to be of less concern to students during the period of the COVID-19 pandemic. In contrast to e-learning acceptance before the COVID-19 pandemic, existing research evidence showed that students’ acceptance of e-learning was significantly affected by how easy or difficult they perceived its usage (Larmuseau et al 2018 ; Yuen and Ma 2008 ). Besides, TAM (Davis 1989 ) posits that when students find a technology to be easy to use, they will as well use it and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the literature, the impact of PU on SAT [100], USE [101], and ACP [10] is significant. Such findings indicate that students are inclined to use the e-learning system if the system provides useful features that facilitate the completion of learning-related tasks efficiently and successfully.…”
Section: Discussionsupporting
confidence: 83%
“…Almaiah and Alismaiel (2019) suggested that perceived usefulness is a crucial factor affecting the use of information systems, and users will use a system if they find it beneficial for their performance. Furthermore, prior research established the statistically positive impact of perceived usefulness on actual use (Alenazy et al, 2019;Algunto et al, 2017;Larmuseau et al, 2018). Thus, the following hypothesis is posited:…”
Section: / 15mentioning
confidence: 96%